NACIÓN, FÚTBOL E IMAGEN PUBLICITARIA: LOS SIGNIFICADOS DE LA COPA AMÉRICA DEL 2001 EN COLOMBIA - Celis Hernández, Marlon Steve (2018)
This article addresses the construction of the idea of nation from the advertising image in the context of the America Cup of 2001. This competition was made in Colombia in parallel with a peace process denominated the Peace Cup, thus allowing, in a sense as a sign expressed in the image through the linguistic message, a denoted image and a connoted image. The methodology was documentary review from Sociology and Semiology.